Evaluasi Kebergunaan Aplikasi Soeselo Online Menggunakan Metode System Usability Scale (SUS), Sauro-Lewis CGS, dan Adjective Rating - Haries Anom Susetyo Aji Nugroho (Infotek: Jurnal Informatika dan Teknologi, 2025)
The development of information technology in the health sector encourages hospitals to adopt application-based registration systems to improve service efficiency. RSUD dr. Soeselo Tegal Regency developed the Soeselo Online application as a solution to reduce physical queues. However, the low rating and many user complaints on the Play Store indicate potential usability problems. This study aims to evaluate the usability of the Soeselo Online application from the user's perspective. The evaluation was conducted using the Usability Testing approach using System Usability Scale (SUS), Completion Rate, Sauro-Lewis Curved Grading Scale (CGS), and Adjective Rating methods. A total of 25 respondents participated in this study. The results of the analysis show that the application has an effectiveness rate of 97.6% which falls into the “Good” category, as well as an average SUS score of 70.3 which falls into the “B” category on the CGS and “Ok” on the Adjective Rating. This finding shows that although the application is quite effective to use, there are aspects of usability that need to be improved to achieve an optimal level of user satisfaction. The results of this study are expected to be the basis of recommendations for further development of the Soeselo Online application in order to improve the quality and user satisfaction of the application, as well as for the hospital in optimizing digital-based services.